High pressure synthesis of single crystals of α-boron - Parakhonskiy, Gleb; Dubrovinskaia, Natalia; Dubrovinsky, Leonid; Mondal, Swastik; van Smaalen, Sander (Journal of crystal growth, 2011)
A method of synthesis of single crystals of alfa-boron (α-B) is presented. α-Boron has been crystallized from a boron-platinum melt at high pressures (6-11GPa) and high temperatures (1200-1600°C). The method is based on the high-pressure large volume (multi-anvil) press technique. An average size of the as-grown isometric crystals is 60-80μm in maximum dimension. A refinement of an accurate crystal structure of α-B against single crystal X-ray diffraction data demonstrates the excellent quality of the single crystals. The crystal structure is in good agreement with the literature.